PENDIDIKAN TERPADU DAN PENGEMBANGAN KREATIVITAS - Nanang Nuryanta (Islamic University of Indonesia, 2002)
The concept of the integrated education emerges can be regarded as a process to discover the profile of ideal education. Actually, the term focusing on how to form the model of education that combining various aspects of potentials of learners. The aspects involve the cognition, affection, psychomotor, and the combination among the talent